Cataloging and classification for library technicians - Kao, Mary Liu (Haworth Press, 2001)
Library technicians will find many helpful features in Cataloging and Classification for Library Technicians, Second Edition, including: definitions of relevant terminology, review questions to focus learning, a list of suggested readings, routines and responsibilities of library technicians, issues and trends in library cataloging and classification, detailed tables and figures to enable easier learning, many onvenient Web addresses for up-to-date information.